Answer:
x^6-9 = x^-3 = 1/x^2
Step-by-step explanation:
Answer:
(a+b)^2 = a^2 + 2ab + b^2
(a-b)^2 = a^2 - 2ab + b^2
(a-b)(a+b) = a^2 - b^2
Step-by-step explanation:
9514 1404 393
Answer:
Step-by-step explanation:
The conjugate is found by changing the sign of the square root term.‡ (For this purpose, i = √-1.)
a) the sign of 3i is changed: 2 + 3i
b) the sign of sqrt(-5) is changed: 8 -sqrt(-5) = 8 -i√5
c) the sign of 2i is changed: 7 +2i
d) the sign of sqrt(7) is changed: 4 +√7
_____
‡ Actually, the conjugate of a binomial is formed by changing the sign <em>between</em> terms. The purpose is to allow the product of the binomial and its conjugate to be the difference of squares.
Conventionally, the conjugate of a complex number is the value with the sign of the imaginary part reversed. That is why (-2i+7)* = 7+2i.
Answer:
Bạn không tử tế :) Đó là một trò đùa
Step-by-step explanation:
Đi qua
Answer: this question may be easier to answer if you actually graph it. You can also use the app Desmos on the AppStore which is free to find the solution.
Step-by-step explanation: